♡ The Question ♡
・3 (x + 4) = x - 8 - 2x
*୨୧ ┈┈┈┈┈┈┈┈┈┈┈┈ ୨୧*
* ♡ The Answer ♡
・x = -5
*୨୧ ┈┈┈┈┈┈┈┈┈┈┈┈ ୨୧*
♡ The Explanation/Step-By-Step ♡
・3 (x + 4) = x - 8 - 2x
3 (x + 4) = x - 2x - 8
3 (x + 4) = -x - 8
3 (x + 4): 3x + 12
Apply the distributive law! : a(b + c) = ab + ac
a = 3, b = x, c = 4
= 3x + 3 x 4
Multiply: 3 x 4 = 12
= 3x + 12
3x + 12 = -x - 8
Subtract 12 from both sides!
3x + 12 - 12 = -x - 8 - 12
Simplify!
3x = -x - 20
Add x to both sides!
3x + x = -x - 20 + x
Simplify!
4x/4 = -20/4
Simplify 4x/4 : x
Divide the numbers!
4/4 = 1 = x
Simplify!
-20/4 : -5
-20/4
Apply the fraction rule! : -a/b = -a/b
= -20/4
Divide the numbers!
20/4 = 5
= -5
x = -5
*୨୧ ┈┈┈┈┈┈┈┈┈┈┈┈ ୨୧*
*♡ Tips ♡
・No tips provided!